Dialectical behavioral therapy skills training in assisted living: transdiagnostic effects on goal attainment, self-efficacy, and symptom severity - Koziol, Philipp; Florin, Carina; Heft, Kathleen; Fellinger, Robert; Probst, Thomas (Frontiers in Psychiatry, 2025)
BackgroundDialectical Behavior Therapy Skills Training (DBT-ST) is an evidence-based intervention targeting emotion regulation, self-efficacy, and psychological well-being. While widely applied in clinical settings, its effectiveness and feasibility in long-term residential care remain underexplored. This study hypothesized that an 8-week DBT-ST program would increase goal attainment and self-efficacy, and decrease psychological distress among assisted living residents, with further improvements expected at a two-week follow-up.MethodA total of 52 residents from four assisted living facilities operated by Pro Mente Salzburg, Austria, participated in an 8-week DBT-ST program. The intervention was delivered by the facilities’ psychologists and by staff supervised by psychologists in weekly group sessions. Self-reports were used to assess goal attainment (ranging from 0% to 100% in 10% intervals), self-efficacy (Self-Efficacy Scale – Short Form; ASKU), and psychological distress (Kessler Psychological Distress Scale; K10).ResultsGoal attainment (p = .040, d = 0.28) and psychological distress (p =.034, d = 0.26) showed initial improvements from baseline to post-intervention, but these effects did not withstand Bonferroni correction. No significant changes were observed between post-intervention and follow-up.ConclusionsWhile nominal improvements were observed, these did not remain significant after correction for multiple testing. The study nonetheless offers preliminary evidence on the feasibility and the challenges of DBT-based interventions in assisted living settings and highlights the need for future research on their context-sensitive adaptations.